The effect of sleeping position on heart rate variability in newborns - Petja Fister; Manca Nolimal; Helena Lenasi; Matjaž Klemenc (BMC, 2020)
Abstract Background Lower heart rate variability (HRV) in a newborn might represent a risk factor for unfavourable outcome, a longer recovery after illness, and a sudden infant death. Our aim was to determine whether the newborn's sleeping position is associated with HRV. Methods We performed a prospective clinical study in 46 hospitalized cardiorespiratory stable term newborns. During sleeping, we measured the parameters of HRV in four body positions (supine, supine with tilt, prone, prone with tilt). Results The TP (total power spectral density) was significantly higher when lying supine in comparison to prone (p = 0,048) and to prone with tilt (p = 0,046). The HF (high frequency of power spectral density) in the supine position without tilt tended to be higher compared to prone without tilt (p > 0,05). The LF (low frequency power) was significantly higher when lying supine compared to prone, both without tilt (p = 0,018). TP and HF showed a positive correlation with gestational but not postmenstrual age (p = 0.044 and p = 0.036, respectively). Conclusions In term newborns, sleeping position is associated with HRV. Higher TP and HF were found in the supine position, which might reflect better ANS stability. Gestational age positively correlated with TP and HF power, but only in supine position. Trial registration ISRCTN11702082 , date of registration: March, 13th, 2020; retrospectively registered.